Tren Prevalensi dan Insidensi Demam Berdarah Dengue (DBD) Global Tahun 2021– 2023: Analisis Data Global Burden of Disease (GBD) - Muhammad Isa; Utami Utami; Vita Widyasari (Universitas Muhammadiyah Manado, 2026)
Dengue Hemorrhagic Fever remained a major public health problem in tropical countries, including Indonesia. This study aimed to analyze trends in prevalence, incidence, and geographical disparities of dengue hemorrhagic fever in Indonesia from 2021 to 2023 using Global Burden of Disease data. A descriptive observational design with a longitudinal approach was applied to analyze national and provincial-level prevalence, incidence, and disease burden. The results showed that dengue prevalence and incidence at the national level gradually declined during the study period, although the magnitude of decline was relatively small. Significant geographical disparities persisted, with higher disease burden observed in several provinces in Sumatra, Kalimantan, and eastern Indonesia. Environmental conditions, population density, and unequal access to health services were considered important contributors to these variations. This study concluded that despite improvements in national dengue control efforts, region-specific and targeted interventions remained essential to reduce disease burden and minimize interprovincial disparities in Indonesia.